A Modified Steffensen Iterative Method with Fourth-order Convergence - WEI Jia; HUANG Jia-yue (Journal of Harbin University of Science and Technology)
A new fourth-order convergent iterative method formed by Newton’s method and Steffensen method is presented to solve nonlinear equations in this paper． The new iteration formula uses derivative of quadratic interpolation as substitute for derivative of function，so it is totally free from derivatives． Furthermore，this method requires only three evaluations of the function by each iteration．